The use of simple analytical techniques to assess surface oxidation of sulphide ores - Sibiya, Ayanda Sikhona (Department of Chemical Engineering, 2024)
Surface oxidation is known to have a negative impact on the flotation performance of sulphide minerals. This is because severe oxidation makes it more difficult to process low-grade sulphide minerals, which reduces the recovery of valuable minerals during flotation. It may be possible to quantitatively correlate the rate/level of oxidation to oxidized sulphide ores using simple surface analytical techniques. This, if done well, could eliminate the need for numerous mineralogical tests, saving both time and money. This study investigated the Ethylenediaminetetraacetic acid (EDTA) Extraction Technique and Reactivity Number (RN) Technique as possible techniques to quantitatively describe oxidation levels in different ore types with different mineral compositions and grade. The aim was to determine if the changes in the surface character generated by oxidation are linked to a measurement obtained from the selected techniques. In the thesis, the techniques were validated on fresh ores of differing grades, Impala UG2 referred to as Ore A and High-grade copper ore referred to as Ore B. The two ores were ground to generate varying particle size distributions and liberation profiles to study the link between oxidation, particle size and liberation. Based on ore type and sulphide liberation, the tests attempted to provide an indicator of feed grade and surface oxidation. Flotation is used as a diagnostic tool. For Ore A, results showed that the grind size 60 % -75 µm yielded the highest Cu recovery, the coarsest grind size 40 % -75µm yielded the second highest Cu recovery, and the grind 80 % -75µm yielded the lowest Cu recovery. Overall, the Ore A results showed that where the grind sizes had high reactivity (high RN OCF) and high EDTA value, poor flotation recovery was observed and where the OCF and EDTA values were lower, favourable recoveries were obtained. EDTA and RN numbers therefore aided in giving an indication of the extent of oxidation that the ore had undergone, which ultimately translated to flotation recoveries. The grind size 80 % -75µm had clearly suffered significantly more oxidation than the other grind sizes and this was indicated by the high OCF and the EDTA value and low Cu recoveries. The liberated Base Metal Sulphides (BMS) for Ore B was generally consistent throughout the three grind sizes, however, the highest Cu recovery was achieved by the grind size 80 % -75µm (95.11 %), followed by grind sizes 60 % -75µm and 40 % -75µm respectively (92.25 % and 90.86 %). The recovery of this ore increases as the grind size becomes finer. Ore B demonstrated that, while the OCF and EDTA value for ore B increased as the grind size became finer, so did the recovery. It is possible that the particles that were ground to achieve particle size 80 % -75µm were at their most hydrophobic state, owing to the increased liberation of the BMS, particularly chalcopyrite.